Comportamento dos aços peritéticos durante a solidificação no molde de lingotamento contínuo - Leonardo Jose Silva de Oliveira (2009)
Many studies have been performed in order to define the main causes and to propose a mechanism for the formation of surface defects in the continuous casting slabs. Therefore, it is very important to understand the heat flux and the initial steel shell formation inside the mold. Still regarding the slab quality, the peritectic steels show the highest surface defect index leading to irregularities along the shell, that occur due to adifference of densities between ferrite delta and austenite phases after solidification. There are significant difficulties to study the initial stage of solidification in the mold. The mold is not accessible and very sensitive to disturbance. Also, owing to many operational variables in continuous casting, it is difficult to conduct industrial experiments with good control of them. Thus, in the present work, an experimental apparatus to study the steel solidification was developed and used to simulate severalconditions of heat extraction in the mold. Using this experimental apparatus, it was also proposed a methodology to evaluate steel shrinkage during the solidification. Three peritectic steel grades were evaluated using the experimental apparatus. The results showed that when peritectic steels are processed under high solidification ratesthe steel shell is not homogeneous. It was also observed that the mould powders exert a great influence in the control of the heat transfer and they are a very important tool to control the casting of peritectic steels. With regard to shrinkage, it was observed that the heat extraction has a significant effect on the intensity of contraction of the peritecticsteels. Higher heat extraction rates increase the intensity of the solidification shrinkage.